Voluntary vasectomy rethinking "Pagkalalaki" among married cebuano - Aguilar, Elmira Judy T. (Philippine Population Review, 2006)
This qualitative study intends to determine the ways in which concepts of masculinity have shaped the contraceptive choice of men for vasectomy. The findings show that masculinity is defined as being responsible husband and father who can provide for the basic needs of his family such as food, clothing, and education. Thus, men's direct participation in family planning is basically due to economic reasons because of his responsibility to take care of his familys' future.